Deletion of the WNK3-SPAK kinase complex in mice improves radiographic and clinical outcomes in malignant cerebral edema after ischemic stroke. Issue 2 (February 2017) - Zhao, Hanshu; Nepomuceno, Rachel; Gao, Xin; Foley, Lesley M; Wang, Shaoxia; Begum, Gulnaz; Zhu, Wen; Pigott, Victoria M; Falgoust, Lindsay M; Kahle, Kristopher T; Yang, Sung-Sen; Lin, Shih-Hua; et al.
The WNK-SPAK kinase signaling pathway controls renal NaCl reabsorption and systemic blood pressure by regulating ion transporters and channels. A WNK3-SPAK complex is highly expressed in brain, but its function in this organ remains unclear. Here, we investigated the role of this kinase complex in brain edema and white matter injury after ischemic stroke. Wild-type, WNK3 knockout, and SPAK heterozygous or knockout mice underwent transient middle cerebral artery occlusion. One cohort of mice underwent magnetic resonance imaging. Ex-vivo brains three days post-ischemia were imaged by slice-selective spin-echo diffusion tensor imaging magnetic resonance imaging, after which the same brain tissues were subjected to immunofluorescence staining. A second cohort of mice underwent neurological deficit analysis up to 14 days post-transient middle cerebral artery occlusion. Relative to wild-type mice, WNK3 knockout, SPAK heterozygous, and SPAK knockout mice each exhibited a >50% reduction in infarct size and associated cerebral edema, significantly less demyelination, and improved neurological outcomes. We conclude that WNK3-SPAK signaling regulates brain swelling, gray matter injury, and demyelination after ischemic stroke, and that WNK3-SPAK inhibition has therapeutic potential for treating malignant cerebral edema in the setting of middle cerebral artery stroke.